Strategi Mekanisme Survival Keluarga Buruh Petani Garam dalam Memenuhi Kebutuhan Hidup (Studi Kasus di Desa Gersik Putih, Gapura - Sumenep) - Maulidina, Erika Yenny; Dzulkarnain, Iskandar; Jamilah, Jamilah (Journal of Linguistics and Social Studies, 2025)
This study examines the Strategy of the Survival Mechanism of Salt Farmers' Families in Meeting the Needs of Life in Gersik Putih Village, Sumenep Regency. The survival strategy is carried out by the family of salt farmer workers to be able to survive and to meet their daily needs. The strategies carried out are active strategies, passive strategies and network strategies. The participation of family members of salt farmer workers can increase the family's economy and can meet needs. In this study using a sociological study of the theory of Survival Mechanism according to James C Scott. The purpose of this study was to find out how the Strategy of Survival Mechanism for Salt Farmers in Meeting the Needs of Life in Gersik Putih Village, Sumenep Regency. Where a farmer does several ways to survive in crisis conditions. Meanwhile, according to James C Scott, tying a tight belt means applying a frugal lifestyle, asking for help from relatives, taking advantage of social relations. The majority of the people of Gersik Putih Village work as salt farmers with difficult economic backgrounds, low education, and are also hereditary jobs. This research uses descriptive qualitative research with a case study approach. Methods of collecting data by means of observation, interviews and documentation. Informants were selected using purposive sampling. Data analysis uses data reduction, data presentation, and drawing conclusions. The technique of checking the validity of the data uses source triangulation.